STRATEGI PENGEMBANGAN KEPARIWISATAAN KOTA PEKANBARU TAHUN 2011-2013 - Syari, Anggi Regia Coolyear; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
According to Olsen and Eadie (in Bryson 2000), strategic planning is a disciplined effort in to make decisions and actions that shape and guide how to become an organization, what the organization, and why organizations do things like that. Pekanbaru is one of the areas that carry out governance and development direction and specific goals to be achieved through development in all areas, including the field of tourism sector. The method used in this research is descriptive method is a qualitative approach to this research will provide a picture or describe in a systematic, factual and accurate to the object to be studied. Based on the results of research through interviews and observation. Strategies of Tourism Arts and Culture in the developing of Tourism has been implemented properly, can be seen from the object and the development of a tourist attraction by providing arts and cultural development of the region and conduct organizing festivals and arts and culture events in the area.Keywords : Strategy, Organization, Tourism.